Asymptomatic Cardiac Manifestations in Hypothyroidism- An Observational Study - Jitender Sharma; Vikas Kumar; Anmol Sharma; Aditya Puniyani (Journal of Nature and Science of Medicine)
Background: Hypothyroidism, affects approximately 11% of adults in India, leading to significant metabolic and cardiovascular dysfunction. This study aimed to assess the prevalence of asymptomatic cardiac anomalies in newly diagnosed hypothyroid patients using echocardiographic screening and to contextualize these findings within clinical practice. Methodology: A cross-sectional observational study was conducted over 10 years at a tertiary care hospital in Northern India, enrolling 200 patients with a primary diagnosis of hypothyroidism. Patients with secondary or subclinical hypothyroidism, preexisting cardiac conditions, or other comorbidities were excluded. Comprehensive clinical evaluations, blood tests, electrocardiogram, and 2D echocardiography were performed to detect systolic and diastolic dysfunction, pericardial effusion, and structural abnormalities. Statistical analysis was conducted using SPSS v22, employing descriptive metrics and proportions. Results: The mean age of the cohort was 37.65 years, with a female preponderance (77%). Common symptoms included weight gain (50%), lethargy, and menstrual irregularities (30%). Echocardiography revealed normal results in 15% of cases, while 26% demonstrated diastolic dysfunction, primarily moderate, and 20% exhibited pericardial effusion. Bradycardia and prehypertension were observed in 20% and 24% of patients, respectively, with interventricular septal thickening noted in 20 cases. Conclusion: This study underscores the high prevalence of subclinical cardiac anomalies in hypothyroidism, emphasizing the need for routine cardiovascular screening in newly diagnosed patients. Early detection and management can mitigate progression to overt cardiovascular morbidity. Future long-term studies are essential to evaluate these findings’ impact on mortality, morbidity, and overall clinical practice.